Thermal Lamination of Electrospun Nanofiber Membrane with Woven Fabric and Yarn Embedding Effect - Ziyuan Gao; Le Xu; Hongxia Wang; Xin Wei; Kaikai Chen; Wenyu Wang; Suzhen Zhang; Tong Lin (Membranes)
This study investigated the effectiveness of two lamination methods for integrating electrospun nanofiber membranes with woven nylon fabric for personal protective applications. The first method used a thermoplastic urethane (TPU) nonwoven adhesive, while the second method incorporated both the adhesive and a yarn, with the yarn embedding by sewing. Lamination with the TPU nonwoven adhesive slightly improved the adhesion between the nanofiber membrane and the nylon fabric. However, it decreased the air permeability, with the degree of the decrease depending on the areal density of the TPU adhesive. As the areal density of the TPU increased from 10 g/m2 to 30 g/m2, the air permeability decreased from 107.6 mm/s to 43.4 mm/s. The lamination resulted in a slight increase in the filtration efficiency for oil aerosol particles (0.3 µm, PM0.3, at a flow rate of 32 L/min) to 96.4%, with a pressure drop of 83 Pa. Embedding non-fusible yarns in the laminate increased the nanofiber/fabric adhesion and permeability. Still, the filtration efficiency and pressure drop were reduced to 74.4% and 38 Pa, respectively, due to numerous pinholes formed in the nanofiber layer during the sewing process. Conversely, incorporating fusible TPU yarns not only improved the interlayer adhesion by 175% compared to using TPU fabric adhesive alone but also increased the air permeability to 136.1 mm/s. However, the filtration performance (87.7%, 72 Pa) was slightly lower than that of the unlaminated nanofiber/fabric pack because the TPU yarns sealed the pinholes during lamination. Lamination embedded with hot-melt yarns provides a versatile approach for combining nanofiber membranes with conventional fabrics. It can be used to develop nanofiber-functionalized textiles for a wide range of applications, including fire protection, electrical insulation, sound absorption, filtration, marine applications, and more.